Genetic Diversity of Virulent Polymyxin-Resistant Klebsiella aerogenes Isolated from Intensive Care Units - Kesia Esther da Silva; Gleyce Hellen de Almeida de Souza; Quézia Moura; Luana Rossato; Letícia Cristina Limiere; Nathalie Gaebler Vasconcelos; Simone Simionatto (MDPI AG, 2022)
This study evaluated the scope and genetic basis of polymyxin-resistant Klebsiella aerogenes in Brazil. Eight polymyxin-resistant and carbapenemase-producing K. aerogenes strains were isolated from patients admitted to the ICU of a tertiary hospital. Bacterial species were identified by automated systems and antimicrobial susceptibility profile was confirmed using broth microdilution. The strains displayed a multidrug resistant profile and were subjected to whole-genome sequencing. Bioinformatic analysis revealed a variety of antimicrobial resistance genes, including the blaKPC-2. No plasmid-mediated colistin resistance gene was identified. Nonetheless, nonsynonymous mutations in mgrB, pmrA, pmrB, and eptA were detected, justifying the colistin resistance phenotype. Virulence genes encoding yersiniabactin, colibactin, and aerobactin were also found, associated with ICEKp4 and ICEKp10, and might be related to the high mortality observed among the patients. In fact, this is the first time ICEKp is identified in K. aerogenes in Brazil. Phylogenetic analysis grouped the strains into two clonal groups, belonging to ST93 and ST16. In summary, the co-existence of antimicrobial resistance and virulence factors is deeply worrying, as it could lead to the emergence of untreatable invasive infections. All these factors reinforce the need for surveillance programs to monitor the evolution and dissemination of multidrug resistant and virulent strains among critically ill patients.